STUDY ON THE LEVEL OF ENGLISH LANGUAGE SKILLS IN THE AGRICULTURAL SECTOR. CASE STUDY - Elena LASCAR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of this study is to find out the level of English language skills and knowledge of the persons who work in the agricultural sector. The young graduates graduate a faculty knowing very well a foreign language. The effort to learn foreign languages must be made daily, especially for the persons in the agricultural sector who get in touch with foreigners and develop international business affairs. A foreign language is the key for communication. The study was carried out based on a questionnaire on 50 respondents with the occupation in the rural area. The questions were clear, easy to understand and the answers to the questionnaire provide information about the English language skills of the persons who work in the agricultural sector and the modalities to improve their language skills in the future. The respondents were from 5 communes in Calarasi County. From this study, we draw the conclusion that English language is important for the persons in the agricultural sector, those who have farms, associations in the agricultural area, as they can extend their business, they can form partnerships with foreigners and gains new experience from them